Case Report: A novel KRT74 variant in an eight-year-old boy with alopecia totalis successfully treated with baricitinib - Tan, Yidong; Yang, Jinxiang; Chen, Xuanyi; Shen, Yihang; Wu, Zhe; Zhou, Weinan; Yao, Zhirong; Zhao, Jingjun; Liang, Jianying (Frontiers in Medicine, 2025)
Alopecia areata is an autoimmune condition characterized by non-scarring hair loss, with genetic factors playing a significant role in disease susceptibility. We report the case of an 8-year-old boy with alopecia totalis harboring a heterozygous KRT74 variant. While his mother and brother share this variant, they do not exhibit alopecia. Immunofluorescence analysis revealed increased phosphorylation of the JAK1-STAT1 pathway and elevated T cell infiltration, predominantly CD4+ T helper cells, in the proband’s scalp. The patient responded favorably to baricitinib treatment (2 mg/day), showing significant hair regrowth within 1 month and continued improvement over 8 months. This case suggests that KRT74 variants may contribute to immune dysregulation in alopecia areata, highlighting the potential role of JAK inhibitors in genetically predisposed alopecia cases.